Implementation and Evaluation of a Mobile Retinal Image Acquisition System for Screening Diabetic Retinopathy - Rêgo, Sílvia (2022)
Funding Information: This work was supported by EyeFundusScopeNEO: Demonstration of EyeFundusScope with Non-Expert Ophthalmology Users, cofounded by Portugal 2020, framed under the Operational Program Competitiveness and Internationalization (COMPETE 2020) and European Regional Development Fund from European Union, with operation code POCI-01-0247-FEDER-038400. Publisher Copyright: © 2022 by the authors.